Study guides

☆☆

Q: X2 plus 6x-2 equals 0

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

15x2-56 = 88+6x2 15x2-6x2-56-88 = 0 9x2-144 = 0 Divide all terms by 9:- x2-16 = 0 (x-4)(x+4) = 0 x = 4 or x = -4

6x2-24=0 6(x2-4)=0 x= {-2,2}

x = -5 x = 2

x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.

x2+8x+12 = 0 When factorized: (x+6)(x+2) = 0 Therefore: x = -6 or x = -2

Related questions

6x2 - 24 = 0 6x2 = 24 x2 = 4 x = (+/-) 2 --------------

10x2 - 64 = 36 + 6x2; whence, 4x2 - 100 = 0, x2 = 25, and x = ±5.

6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.

x2 + 36x = 0 x2 = -36x x = -36

15x2-56 = 88+6x2 15x2-6x2-56-88 = 0 9x2-144 = 0 Divide all terms by 9:- x2-16 = 0 (x-4)(x+4) = 0 x = 4 or x = -4

6x2-24=0 6(x2-4)=0 x= {-2,2}

no

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

-2

x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

People also asked